Crop Conversion from Annual to Perennials: An Effective Strategy to Affect Soil Multifunctionality - Liu, Panpan; Wang, Dong; Li, Yue; Liu, Ji; Cui, Yongxing; Liang, Guopeng; Wang, Chaoqun; Wang, Chao; Moorhead, Daryl L.; Chen, Ji (Agronomy (Basel), 2024)
Although crop conversion from annual to perennial crops has been considered as one path towards climate-smart and resource-efficient agriculture, the effects of this conversion on soil multifunctionality and biomass yields remain unclear. The objective of the study is to enhance soil multifunctionality while exerting a marginal influence on farmer income. Here, we investigated the effects of annual winter wheat (Triticum aestivum L.) and two perennial crops (a grass (Lolium perenne L.), a legume (Medicago sativa L.), and their mixture) on soil multifunctionality and biomass yield on the Yellow River floodplain. Soil multifunctionality was assessed by the capacity of water regulation and the multifunctionality of carbon (C), nitrogen (N), and phosphorus (P) cycles. C cycle multifunctionality index is the average of β-xylosidase, β-cellobiosidase, and β-1, 4-glucosidase. N cycle multifunctionality index is the average of L-leucine aminopeptidase and β-1, 4-N-acetyl-glucosaminidase, and acid phosphatase represented (and dominated) P cycle functions. The results showed that perennial crops enhanced soil multifunctionality by 207% for L. perenne, 311% for M. sativa, and 438% for L. perenne + M. sativa, compared with annual winter wheat (T. aestivum). The effect of perennial crops on soil multifunctionality increased with infiltration rate, dissolved organic C, microbial biomass C, and extracellular enzymatic activities for both C and N acquisition. However, we observed that perennial crops had a lower biomass yield than annual crop. Therefore, the transition of agricultural landscapes to perennials needs to take into account the balance between environmental protection and food security, as well as environmental heterogeneity, to promote sustainable agricultural development.